2017
DOI: 10.4317/jced.54404
|View full text |Cite
|
Sign up to set email alerts
|

Color stability of CAD/CAM Zirconia ceramics following exposure to acidic and staining drinks

Abstract: BackgroundThe aim of this in vitro study was to evaluate the color stability of CAD/CAM Zirconia ceramics following exposure to acidic drink (Coca Cola) and after exposure to staining solution (coffee).Material and MethodsAll the samples were immersed in different staining solutions over a 28-day test period. A colorimetric evaluation according to the CIE L*a*b* system was performed by a blind trained operator at 7, 14, 21, 28 days of the staining process. Shapiro Wilk test and Kruskal-Wallis ANOVA were applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 23 publications
6
44
0
2
Order By: Relevance
“…This could be explained by the acid-resistant property of zirconia ceramics, which could have shown less vulnerability for discoloration. Similar to the outcome of the present study, Colombo et al also observed clinically acceptable color values with zirconia specimens following one week of storage in a Coca-Cola beverage [15]. Furthermore, in a study by Derafshi et al, it was found that zirconia specimens stored in mouth rinses exhibited clinically acceptable ΔE values [17].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This could be explained by the acid-resistant property of zirconia ceramics, which could have shown less vulnerability for discoloration. Similar to the outcome of the present study, Colombo et al also observed clinically acceptable color values with zirconia specimens following one week of storage in a Coca-Cola beverage [15]. Furthermore, in a study by Derafshi et al, it was found that zirconia specimens stored in mouth rinses exhibited clinically acceptable ΔE values [17].…”
Section: Discussionsupporting
confidence: 90%
“…Following the 28-day study period, GB specimens stored in the coffee solution showed marked changes compared to other specimens. Similarly, for zirconia specimens immersed in the coffee solution in previous studies, higher than clinically acceptable values were reported [15][16].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…For the interpretation of the clinical data, according to various articles, a ΔE value superior to 3.3 is visually appreciable by a nonskilled person, which means that the color change is unacceptable in the context of aligners worn for aesthetic reasons [25,26]. If the ΔE value is smaller than 1, it is considered clinically undetectable (values between 1 and 3.3 are deemed clinically acceptable) [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…These insults could affect the color stability of restorations in oral service due to repeated exposure over time. The overall success rate of these different restorations is measured in terms of mechanical and aesthetic stability over time 1,2 .…”
Section: Introductionmentioning
confidence: 99%